Letters to a young theologian - Van der Westhuizen, Henco (Sun Media, 2022)
Theology is, for many, far more than a profession. It is an identity, a passion, a way of life. While books on theology are countless, books on the identity of the theologian are all too rare. In this helpful volume, Henco van der Westhuizen has assembled an outstanding and diverse array of theologians who each offer their wisdom and reflection on what it means to be a theologian through a letter written to someone considering the field. Each letter is as uniq.